2003
DOI: 10.1038/sj.bjc.6601393
|View full text |Cite
|
Sign up to set email alerts
|

Defects in death-inducing signalling complex formation prevent JNK activation and Fas-mediated apoptosis in DU 145 prostate carcinoma cells

Abstract: Androgen-independent prostate carcinomas are resistant to chemotherapy and cell lines derived from androgen-independent prostate carcinomas such as DU 145 cells are highly resistant to Fas-mediated apoptosis. The incubation of DU 145 cells with anti-Fas IgM agonistic antibody of Fas receptor fails to activate JNK, a stress kinase involved in regulating apoptosis. We have previously shown that JNK activation is sufficient and necessary to promote Fas-mediated apoptosis in DU 145 cells. We investigate the mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 33 publications
0
5
1
Order By: Relevance
“…Few anticancer reagents work on the hormone-refractory prostate cancer. It is well known that androgen-independent cancer cells are resistant to radiotherapy, chemotherapy, and Fas-mediated apoptosis (Suzuki et al, 2000;Curtin and Cotter, 2003). In this study, however, we observed that ASA in combination with TRAIL effectively induces cytotoxicity to androgen-dependent LNCaP and its derivative androgen-independent cells.…”
Section: Discussioncontrasting
confidence: 48%
“…Few anticancer reagents work on the hormone-refractory prostate cancer. It is well known that androgen-independent cancer cells are resistant to radiotherapy, chemotherapy, and Fas-mediated apoptosis (Suzuki et al, 2000;Curtin and Cotter, 2003). In this study, however, we observed that ASA in combination with TRAIL effectively induces cytotoxicity to androgen-dependent LNCaP and its derivative androgen-independent cells.…”
Section: Discussioncontrasting
confidence: 48%
“…The failure of androgen ablation therapy leads to a hormone‐refractory state of the disease. It is well known that androgen‐independent cancer cells are resistant to radiotherapy, chemotherapy, and Fas‐mediated apoptosis [Suzuki et al, 2000; Curtin and Cotter, 2003]. Nonetheless, previous studies show that DTX is an effective anti‐cancer agent against HRPC [Chowdhury et al, 2007].…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorylated HSPB1 is supposed to interact with Daxx, preventing its translocation to the cytosol, and thus inhibits binding of Daxx to Fas receptor and Daxx-dependent apoptosis (51,52). This suggestion was not confirmed in a recently published paper (70), and one cannot exclude that HSPB1 somehow affects not only the Daxx-dependent pathway but can also affect the FADDdependent activation of caspase-8.…”
Section: H Hspb1 In Apoptosis and Carcinogenesismentioning
confidence: 93%